The effectiveness or Trichoderma spp. On paddy productions; a review / Norrahilah Ahmad - Ahmad, Norrahilah (Faculty of Plantation and Agrotechnology, 2016)
Trichoderma spp. was known as an effective biocontrol agent. The purpose of this study to increase the yield of paddy in ton/ha. Trichoderma spp. functions to reduce the level of disease and also helps the increasing production of paddy. Moreover, the study shows that Trichoderma spp. is a biological control that inhibit target organisms growth by their ability that grow much faster than pathogenic fungi hence competing for nutrient and space. It may affects the development of paddy by increasing the root and shoot in length, increased in plant height, leaf number and tiller number. In the other hand, Trichoderma spp. may help in enhancement of stress environment such in drought condition and also accelerate decomposition of matter. The studied also shown that Trichoderma spp. increases of root surface area due to the application of Trichoderma spp. helps the increase the deep of root in the soil that may increases the water absorption thus reducing the water stress (wilting) and also increasing the nutrient uptake. The most study shown it explain about the role and mechanism of Trichoderma spp. that increasing the paddy productions.